Employee Engagement as a Predictor of Organizational Citizenship Behavior (OCB) in a CV in East Java - Atikah Wahyu Permatasari; Rosita Endang Kusmaryani (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2025)
This study is motivated by the low level of Organizational Citizenship Behavior (OCB), despite a relatively high level of employee engagement, as indicated by employees' responsibility for their work and efforts to seek innovative ideas. The study also aims to examine whether employee engagement can serve as a predictor of Organizational Citizenship Behavior (OCB) among employees in a service company. A quantitative approach was used, employing a survey research design involving 32 randomly selected employees. Data collection was conducted using a modified work engagement scale and an OCB scale. The statistical analysis results indicate that employee engagement does not have a significant simultaneous effect on OCB (p=0.059; R²=23%). Partial tests also show that the dimensions of cognitive engagement, emotional engagement, and behavioral engagement are not significantly related to OCB. In conclusion, employee engagement is not a significant predictor of OCB. The study's findings suggest that employee engagement does not have a simultaneous effect on OCB.